1998
DOI: 10.7164/antibiotics.51.936
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Radicicol as an Inhibitor of In Vivo Ras/Raf Interaction with the Yeast Two-hybrid Screening System.

Abstract: Activation of cytoplasmic serine/threonine kinase Raf-1, an important effector of Ras, requires direct binding to Ras. The yeast two-hybrid screening system used for identification of inhibitors of Ras/Raf-1 interaction showed radicicol to be an inhibitor. Radicicol has been shown to induce morphological reversion of transformed cells. Immunoprecipitation with an anti-Ras antibody revealed that the in vivo Ras/Raf-1 binding in v-Ha-rasbinding of glutathion S-transferase-fused Ras to a maltose binding protein-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…1, C and D). Although these results confirmed our previously published observations (20,21), we now for the first time demonstrate that blocking hyperactive H-Ras with radicicol (56,57) or inhibiting downstream proliferative signaling with Mek/Erk inhibitor, PD98059 (58), as well as inhibition of cdk4 with PD0332991 (59) (Fig. 1E) all resulted in a significant up-regulation in the synthesis of tropoelastin (Fig.…”
Section: Resultssupporting
confidence: 78%
“…1, C and D). Although these results confirmed our previously published observations (20,21), we now for the first time demonstrate that blocking hyperactive H-Ras with radicicol (56,57) or inhibiting downstream proliferative signaling with Mek/Erk inhibitor, PD98059 (58), as well as inhibition of cdk4 with PD0332991 (59) (Fig. 1E) all resulted in a significant up-regulation in the synthesis of tropoelastin (Fig.…”
Section: Resultssupporting
confidence: 78%
“…The 1 H NMR data (Table 1) All isolates were evaluated for their inhibitory activities of Ras-Raf-1 interaction in the yeast two-hybrid assay (Table 2) according to a literature method. 3 In brief, we looked for a compound giving a clear zone of inhibition (ZOI) that inhibited growth of LZ cells in the SD His -plates and not in the SD His + plates, together with inhibition of b-galactosidase activity. This would indicate the compound is an inhibitor of Ras-Raf-1 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…18 Cycloheximide (6) was isolated from the cultures of Streptomyces griseus and has been demonstrated to inhibit protein synthesis in mammalian systems. 3,19 AH-135Y (5) has been reported from Streptomyces albovinaceus is reported to have antiherpetic, cytotoxic and antifungal activities. 9 Many terrestrial yeast, lichens, and fungi are known to produce diketopiperazines by condensation of two amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased expression of gelsolin, an actin regulatory protein, has also been observed during the induction of morphological changes in various transformed cells (11). Recent studies showed that radicicol disrupted the Ras-activated signaling pathway by selectively depleting Raf kinase or reducing Ras/Raf molecular interaction (12,13). The target molecule of radicicol was proposed to be Hsp90, because it strongly binds Hsp90 in a manner competitive with ATP and geldanamycin, a known Hsp90 inhibitor (14,15).…”
mentioning
confidence: 99%